Research on the antibacterial properties of nanoscale zinc oxide particles comprehensive review - Nan, Jiahe; Chu, Yanhui; Guo, Ran; Chen, Peijian (Frontiers in Materials, 2024)
Bacteria are present in the environment around us, including in the air, water, and soil. Moreover, infection-causing bacteria are transmitted indirectly through the air, food, and water, as well as through direct contact. Upon entering the human body, they multiply and cause various discomforts or diseases. To combat such diseases, antibiotics are the current choice of the primary treatment. However, their overuse has led to a major issue referred to as bacterial resistance. Metal NPs possess great potential in microbial detection along with disease diagnosis and treatment. Zinc is an essential trace element crucial for human growth and development, and zinc oxide (ZnO) nanoparticles (NPs) are an inorganic material with broad-spectrum antibacterial activity. Therefore, in this review article, we provide a detailed overview of the antibacterial mechanisms of ZnONPs, thereby providing theoretical support for their application.